Analysis of the implications of digital voting through neutrosophic Delphi modeling - Diego Pablo Palma Rivera; Silvio Amable Machuca Vivar; Bolívar Enrique Villalta Jadan; Misael Abisai Valarezo Bracho (Journal of Fuzzy Extension and Applications)
The modernization of electoral systems through digital technologies, such as electronic voting, has marked significant progress in emerging regions like Santo Domingo de los Tsáchilas, Ecuador. However, these systems still face challenges that have hindered their full acceptance by citizens. This study analyzed key elements to ensure the viability and impact of electronic voting within the local electoral system, employing the neutrosophic Delphi method. Findings indicated that trust in electronic voting is bolstered when security measures are in place, and transparent access to information is provided. Additionally, citizen participation in audits and digital education contributes to greater social acceptance of the system. In conclusion, both digital literacy and transparency are essential in establishing reliability in the system. Future research should focus on enhancing cybersecurity and digital education to foster trust in electronic voting systems further.